2014
DOI: 10.1089/neu.2013.3193
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue Is Neuroprotective against Mild Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a leading cause of death and disability worldwide. Methylene blue (MB) has known energy-enhancing and antioxidant properties. This study tested the hypothesis that MB treatment reduces lesion volume and behavioral deficits in a rat model of mild TBI. In a randomized double-blinded design, animals received either MB (n = 5) or vehicle (n = 6) after TBI. Studies were performed on 0, 1, 2, 7, and 14 days following an impact to the primary forelimb somatosensory cortex. MRI lesion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 46 publications
2
47
0
1
Order By: Relevance
“…The lesion volumes were determined as pixels with T2 values higher than the mean plus two standard deviations of the value in the homologous contralesional region. 23 Preparation of brain tissue and protein determination Tissues from each injured hemispheres were separated after CCI or sham injury, weighed and immediately frozen in liquid nitrogen. Tissue samples from each group were lysed in RIPA Lysis Buffer with a protease inhibitor cocktail (05892791001; Roche, Basel, Switzerland) and homogenized at 4°C until lysis was complete.…”
Section: Mri Protocolmentioning
confidence: 99%
“…The lesion volumes were determined as pixels with T2 values higher than the mean plus two standard deviations of the value in the homologous contralesional region. 23 Preparation of brain tissue and protein determination Tissues from each injured hemispheres were separated after CCI or sham injury, weighed and immediately frozen in liquid nitrogen. Tissue samples from each group were lysed in RIPA Lysis Buffer with a protease inhibitor cocktail (05892791001; Roche, Basel, Switzerland) and homogenized at 4°C until lysis was complete.…”
Section: Mri Protocolmentioning
confidence: 99%
“…Note that the lesion volume and behavioral measures data from vehicle and acute MB treatment groups have been previously published. 25 T 2 , ADC, FA, and CBF in the acute MB treatment group have not been previously published.…”
Section: Animal Preparationmentioning
confidence: 99%
“…3) Histological data were not included in the current study given that we have previously reported such data and found no significant difference in lesion volume detected by MRI and Nissl or Fluro Jade immunohistology. 25 Future studies will include assessment of neurodegeneration and markers of inflammation.…”
Section: Limitations Of the Current Studymentioning
confidence: 99%
See 2 more Smart Citations